Simple and Low‐Cost Sampling of Cell‐Free Nucleic Acids from Blood Plasma for Rapid and Sensitive Detection of Circulating Tumor DNA. Issue 10 (30th July 2018) - Jin, Choong Eun; Koo, Bonhan; Lee, Tae Yoon; Han, Kyudong; Lim, Seok Byung; Park, In Ja; Shin, Yong
Abstract: Cell‐free nucleic acids (cfNAs) are emerging diagnostic biomarkers for monitoring the treatment and recurrence of cancers. In particular, the biological role and clinical usefulness of cfNAs obtained from the plasma of patients with various cancers are popular and still intensely explored, yet most studies are limited by technical problems during cfNA isolation. A dimethyl dithiobispropionimidate (DTBP)‐based microchannel platform that enables spontaneous cfNA capture in 15 min with minimal cellular background and no requirements for use of bulky instruments is reported first. This platform identified KRAS and BRAF hot‐spot mutations following cfDNA isolation from the blood plasma and tissues obtained from 30 colorectal cancer patients. The correlation of mutations between the primary tissues and plasma from the patients was high using this platform with whole genome sequencing compared to the spin‐column method. This platform can also be combined with various detection approaches (biooptical sensor, Sanger sequencing, and polymerase chain reaction (PCR)) for rapid, simple, low‐cost, and sensitive circulating tumor DNA detection in blood plasma. The efficiency and versatility of this platform in isolating cfNAs from liquid biopsies has applications in cancer treatment and precision medicine. Abstract : Dimethyl dithiobispropionimidate platform enables spontaneous cell‐free nucleic acid (cfNA) capture in 15 min with less cellular background and no requirement for bulky instruments. This platform can be combined with various detection approaches for rapid, simple, low‐cost, and sensitive circulating tumor DNA detection in blood plasma. The efficiency and versatility of this platform in isolating cfNAs from liquid biopsies can find various cancer applications.